PERATURAN DAN PENGAWASAN PERBANKAN SYARIAH MENURUT PERUNDANG-UNDANGAN INDONESIA - Muhammad Sood; H. Muhaimin; Sumiyati Ismail (Faculty of Law, University of Mataram, 2017)
The purpose of this research is to analyze the regulation and supervision of Sharia banking business according to positive law in Indonesia, while the target is to be achieved, first, to analyze the regulation of Sharia banking supervision institution of according the positive law; Second, the existence of the institution of Sharia banking supervision, comparison of Sharia banking supervision that conducted by Bank Indonesia, the Financial Service Authority (FSA), the Board of Commissioners, and Board of Sharia Supervisory (BSS) according to Indonesian positive law. The gathering of legal materials conducted through the study of literature, then conducted a qualitative descriptive analysis to obtain a prescriptive conclusion deductively. The result of research shows that the regulation and supervision of Sharia banking in Indonesia at first is the authority of Bank Indonesia, then change judicially to become the authority of the FSA. The supervision of Sharia bank internally is also the authority of the Board of Commissioner and ShariaBSS as stipulated in the Banking Law of Sharia and Limited Company Law. Base on the result of research, there are inconsistent or conflict of norm about authority among institutions on regulation and supervision of banking. The problem can cause the legal uncertainty in the implementation of its functions, duties and authority of the FSA as an institution that is mandated by law in conducting regulation and supervision of banking. Therefore, it necessary to regulate comprehensively about Sharia banking supervision in an article or provision clearly and comprehensible, because of there are differences of the characteristics of Sharia banking activities.